Rab39a and Rab39b display different intracellular distribution and function in sphingolipids and phospholipids transport - Gambarte Tudela, Julian Alberto (2019)
Rab GTPases define the identity and destiny of vesicles. Some of these small GTPases present isoforms that are expressed differentially along developmental stages or in a tissue-specific manner, hence comparative analysis is difficult to achieve. Here, we describe the intracellular distribution and function in lipid transport of the poorly characterized Rab39 isoforms using typical cell biology experimental tools and new ones developed in our laboratory. We show that, despite their amino acid sequence similarity, Rab39a and Rab39b display non-overlapping intracellular distribution. Rab39a localizes in the late endocytic pathway, mainly at multivesicular bodies. In contrast, Rab39b distributes in the secretory network, at the endoplasmic reticulum/cis-Golgi interface. Therefore, Rab39a controls trafficking of lipids (sphingomyelin and phospholipids) segregated at multivesicular bodies, whereas Rab39b transports sphingolipids biosynthesized at the endoplasmic reticulum-Golgi factory. Interestingly, lyso bis-phosphatidic acid is exclusively transported by Rab39a, indicating that both isoforms do not exert identical functions in lipid transport. Conveniently, the requirement of eukaryotic lipids by the intracellular pathogen Chlamydia trachomatis rendered useful for dissecting and distinguishing Rab39a-and Rab39b-controlled trafficking pathways. Our findings provide comparative insights about the different subcellular distribution and function in lipid transport of the two Rab39 isoforms.